Exploring the Applicability of Calorespirometry to Assess Seed Metabolic Stability Upon Temperature Stress Conditions—Pisum sativum L. Used as a Case Study - Lénia Rodrigues; Amaia Nogales; Lee D. Hansen; Fátima Santos; Ana Elisa Rato; Hélia Cardoso (Frontiers in Plant Science, 2022)
The availability of phenotyping tools to assist breeding programs in the selection of high-quality crop seeds is of obvious interest with consequences for both seed producers and consumers. Seed germination involves the activation of several metabolic pathways, such as cellular respiration to provide the required ATP and reducing power. This work tested the applicability of calorespirometry, the simultaneous measurement of heat and CO2 rates, as a phenotyping tool to assess seed respiratory properties as a function of temperature. The effect of temperature on seed germination was evaluated after 16 h of seed imbibition by calorespirometric experiments performed in isothermal mode at 15, 20, 25, and 28°C on the seeds of three cultivars of peas (Pisum sativum L.) commonly used in conventional agriculture (cvs. ‘Rondo’, ‘Torta de Quebrar’, and ‘Maravilha d’América’). Significant differences in metabolic heat rate and CO2 production rate (RCO2) as well as in the temperature responses of these parameters were found among the three cultivars. A seed germination trial was conducted during the 6 days of imbibition to evaluate the predictive power of the parameters derived from the calorespirometric measurements. The germination trial showed that the optimal germination temperature was 20°C and low germination rates were observed at extreme temperatures (15 or 28°C). The cv. ‘Torta de Quebrar’ showed significantly higher germination in comparison with the other two cultivars at all three temperatures. In comparison with the other two cultivars, ‘Torta de Quebrar’ has the lowest metabolic heat and CO2 rates and the smallest temperature dependence of these measured parameters. Additionally, ‘Torta de Quebrar’ has the lowest values of growth rate and carbon use efficiency calculated from the measured variables. These data suggest that calorespirometry is a useful tool for phenotyping physiologic efficiency at different temperatures during early germination stages, and can determine the seeds with the highest resilience to temperature variation, in this case ‘Torta de Quebrar’.